A STEM-based e-Book for Scientific Literacy and Sustainability-oriented Learning on Human Digestive System Concepts - Rizky Agassy Sihombing; Noviansyah Kusmahardhika; Shiang-Yao Liu; Chun-Yen Chang (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
The ability to comprehend and apply scientific concepts to contemporary issues is essential for the long-term growth of society. Scientific literacy enables students to understand how their bodies digest food, what it means to eat a balanced diet, and how their food choices affect the environment. The goal of this study was to create and test a STEM-based e-Book about the human digestive system that would help eighth-grade students become more scientifically literate while also teaching them about sustainability. The study utilized a Research and Development (RD) methodology based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Experts in media, learning design, materials, and language confirmed that the product was valid. They showed that the e-Book would perform well in the classroom. Thirty-eight-grade students at a private junior high school in Medan were involved in the implementation. A pretest measured how well something worked. We used pretest and post-test assessments to evaluate the effectiveness. The results showed a significant improvement in students’ scientific literacy. Most of the students scored above the minimum mastery level, with an average N-Gain in the high range (0.75). Feedback from students and teachers indicated that the e-Book was helpful for both classroom and independent learning. The results suggest that integrating STEM principles and sustainability topics into digital learning resources can significantly improve scientific literacy and promote health awareness grounded in sustainability among junior high school students.